Newcastle disease virus: is an updated attenuated vaccine needed?. Issue 5 (3rd September 2018) - Shahar, Ehud; Haddas, Ruth; Goldenberg, Dana; Lublin, Avishai; Bloch, Itai; Bachner Hinenzon, Noa; Pitcovski, Jacob
ABSTRACT: Newcastle disease virus (NDV) is a major cause of infectious mortality and morbidity in poultry worldwide. It is an enveloped virus with two outer-membrane proteins—haemagglutinin-neuraminidase (HN) and fusion protein (F)—that induce neutralizing antibodies. All NDV strains belong to one serotype. Yet, NDV vaccines, derived from genotype II, do not fully prevent infection or shedding of viruses from other genotypes. The aim of this study was to test if an updated vaccine is required. For this purpose, NDVs isolated from infected, albeit heavily vaccinated, flocks were genetically and immunologically characterized. Amino acid differences in F and HN protein sequences were identified between the vaccine strain and each of the isolates, some specifically at the neutralization sites. Whereas all tested isolates showed similar haemagglutination-inhibition (HI) titres, 100–100, 000 times higher antibody-to-virus ratios were needed to neutralize viral propagation in embryos by the field isolates versus the vaccine strain. As a result, a model and an equation were developed to explain the phenomenon of escape in one-serotype viruses and to calculate the HI values needed for protection, depending on variation rate at key positions. In conclusion, to confer full protection against NDVs that differ from the vaccine strain at the neutralizing epitopes, very high levels of antibodies should be raised and maintained to compensate for the reduction in the number of effective epitopes; alternatively, an adjusted attenuated vaccine should be developed—a task made possible in the current era of reverse vaccinology.